On T-Stability of the Picard Iteration for Generalized φ-Contraction Mappings - R. H. Haghi; M. Postolache; Sh. Rezapour (Abstract and Applied Analysis)
We introduce some results on T-stability of the Picard iteration for φ-contraction and generalized φ-contraction mappings on metric spaces.